2013
DOI: 10.1016/j.talanta.2013.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate detection with ammonium nitrate and humic acids as potential interfering substances by pulsed voltammetry technique

Abstract: ElsevierMartínez Gil, P.; Laguarda Miró, N.; Soto Camino, J.; Masot Peris, R. (2013) AbstractPulsed voltammetry has been used to detect and quantify glyphosate on buffered water in presence of ammonium nitrate and humic substances. Glyphosate is the most widely used herbicide active ingredient in the world. It is a non-selective broad spectrum herbicide but some of its health and environmental effects are still being discussed. Nowadays, glyphosate pollution in water is being monitored but quantification tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 31 publications
0
9
1
Order By: Relevance
“…The obtained results ( R 2 > 0.841 RMSEP < 8.23) indicate that PLS modeling for the combination of fermentable sugars is slightly lower than the ones shown in the previous cases. However, these results are not far from those obtained in other scientific studies in similar fields [ 39 , 41 ].…”
Section: Resultscontrasting
confidence: 71%
See 3 more Smart Citations
“…The obtained results ( R 2 > 0.841 RMSEP < 8.23) indicate that PLS modeling for the combination of fermentable sugars is slightly lower than the ones shown in the previous cases. However, these results are not far from those obtained in other scientific studies in similar fields [ 39 , 41 ].…”
Section: Resultscontrasting
confidence: 71%
“…Previous studies suggested using non-oxidizable materials instead of oxidizable ones (e.g., Cu, Co, Ni, Ag) due to their rust resistance and easy handling, avoiding complex cleaning treatments of the electrodes [ 41 , 42 ]. Moreover stainless steel was selected among other non-oxidizable materials (e.g., Pt, Au, Ir, Rh) because of a clear economic motivation and its successful and extended use in food industry applications [ 21 , 28 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A quantification study using PLS was carried out (Laguarda -Miró, et al 2012), (Martínez, et al 2013), (Campos, et al 2010b) in order to evaluate the performance of the system and determine the Limit of Detection for CWA simulants. According to the obtained results in previous classification studies, DCNP was selected as quantification analito due to its high response.…”
Section: Pls Quantificationmentioning
confidence: 99%